Delayed onset of smooth muscle cell differentiation leads to hydroureter formation in mice with conditional loss of the zinc finger transcription factor gene Gata2 in the ureteric mesenchyme. Issue 4 (30th April 2019) - Weiss, Anna‐Carina; Bohnenpoll, Tobias; Kurz, Jennifer; Blank, Patrick; Airik, Rannar; Lüdtke, Timo H; Kleppa, Marc‐Jens; Deuper, Lena; Kaiser, Marina; Mamo, Tamrat M; Costa, Rui; von Hahn, Thomas; et al.
Abstract: The establishment of the peristaltic machinery of the ureter is precisely controlled to cope with the onset of urine production in the fetal kidney. Retinoic acid (RA) has been identified as a signal that maintains the mesenchymal progenitors of the contractile smooth muscle cells (SMCs), while WNTs, SHH, and BMP4 induce their differentiation. How the activity of the underlying signalling pathways is controlled in time, space, and quantity to activate coordinately the SMC programme is poorly understood. Here, we provide evidence that the Zn‐finger transcription factor GATA2 is involved in this crosstalk. In mice, Gata2 is expressed in the undifferentiated ureteric mesenchyme under control of RA signalling. Conditional deletion of Gata2 by a Tbx18 cre driver results in hydroureter formation at birth, associated with a loss of differentiated SMCs. Analysis at earlier stages and in explant cultures revealed that SMC differentiation is not abrogated but delayed and that dilated ureters can partially regain peristaltic activity when relieved of urine pressure. Molecular analysis identified increased RA signalling as one factor contributing to the delay in SMC differentiation, possibly caused by reduced direct transcriptional activation of Cyp26a1, which encodes an RA‐degrading enzyme. Our study identified GATA2 as a feedback inhibitor of RA signalling important for precise onset of ureteric SMC differentiation, and suggests that in a subset of cases of human congenital ureter dilatations, temporary relief of urine pressure may ameliorate the differentiation status of the SMC coat. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.